Impact of the technological resources in the development of the receptive skills in the teaching - learning process of the English language in the senior students at Jambeli and Zoila Ugarte de Landívar high schools in Santa Rosa city, in the academic year 2012 – 2013 - Conza López, José Antonio (2013)
The technological resources are important in the develop of the receptive skills in the education, the teacher need to qualified in the use of them. The teacher knows the use of them. The technological gives more opportunities for provide a teaching easier and the student understands, however through technological tools allow students to be intellectually challenged while providing them with a realistic snapshot of that the modern office looks like.